Public Prosecutors' Authority in Asset Seizure: Institutional Challenges to Asset Recovery in Indonesian Corruption Cases - Satria Zakaria; Mohamad Rusdiyanto U. Puluhulawa; Karlin Z. Mamu; Norsalwati Mohd Razalli (Yayasan Cendekia Gagayunan Indonesia, 2026)
Although Indonesia has strengthened the regulation of corruption crimes, empirical studies on the implementation of the authority of investigating prosecutors in asset confiscation, especially at the regional high prosecutor's office, are still limited. This study aims to analyze the authority of the investigating prosecutor in confiscating assets resulting from corruption at the Gorontalo High Prosecutor's Office and identify factors that hinder its implementation. This study uses a qualitative empirical legal research method with a socio-legal approach. Primary data was obtained through in-depth interviews with prosecutors in the field of special crimes, secondary data was obtained from literature reviews, books, journals and other supporting documents relevant to this research. The results of the study found that although the investigating prosecutor has strong attribution authority to seize corrupt assets, this authority has not been able to produce optimal asset recovery: the 2021–2024 period shows a gap of almost 70% between the total state losses (more than Rp110 billion) and the compensation money that has been successfully recovered (around Rp34 billion). Furthermore, this study found that the biggest obstacle does not come from legal norms, but from weak institutional coordination between the prosecutor's office and related agencies such as banking. These findings confirm that the problem of asset recovery in Indonesia is structural, not just normative. This study recommends strengthening asset forfeiture regulations, improving cross-agency coordination mechanisms, and increasing the technical capacity of investigators.